Pengaruh Model Pembelajaran Problem Based Learning Pada Hasil Belajar Peserta Didik Pembelajaran IPS Kelas VII - Pamungkas, Nur Lambang Tri; Okianna, Okianna; Karolina, Venny (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to see whether there is an effect of problem-based learning on the social studies learning outcomes of seventh grade students. This research used quasi experimental design method with nonequivalent control group design. There were 31 students who became research samples in class VII B as the experimental group, and 31 other students in class VII C as the control group. Data were collected through multiple choice tests consisting of pretest and posttest. The data analysis technique used is the normality test with the shapiro wilk formula and the hypothesis test using the mann whitney u test. Based on the results of data analysis, it was found that class VII B as the experimental group obtained a score of 77.25, while class VII C as the control group amounted to 43.54. There is a significant inequality in both data. The normality test results on the pretest and posttest data of the experimental group and control group were not normally distributed with a value of 0.000. Based on hypothesis testing on the mann-whitney u test of 0.000 <0.05, which means Ha is accepted and Ho is rejected. In addition, the calculation of the effect size test resulted in a value of 0.41 which shows problem-based learning has a positive impact on student learning outcomes compared to conventional social studies learning with a medium category